A case study: an exploration of the implications of computer-assisted audit techniques on the audit approach in terms of the key elements of an assurance engagement. - MacDonald, Darren Kyle (My University, 2019)
Not only has IT become more prominent in the business environment, but it has also expanded the available tools at the auditors’ disposal. These tools are more commonly known as CAATs. The implications of CAATs have not been addressed adequately in the academic environment. As a result, this leads to the purpose of this research report: to illustrate the implications of introducing CAATs in the audit process on the five key elements of an assurance engagement. A case study methodology has been selected to explore this audit approach in great detail by focusing on one client and its audit firm. This methodology has been chosen to illustrate the context of a computerised audit and its specific consequences over a period of time. As a result, this study has managed to demonstrate the benefits from introducing CAATs throughout each key area of the audit process. In order to achieve these benefits, the auditor needs to consider several matters to ensure an efficient IT-based audit is realised.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, In partial fulfillment of the requirements for the degree of Masters of Commerce in Accounting
Keywords: UCTD; CAATs; Data analytics; Audit approach; IT-based audit; Case study; Auditing, Internal--Data processing; Auditing; SDG-8: Decent work and economic growth